Vietnam: A Time of Reckoning - Lahney, Jan (LiNQ (Literature in North Queensland), 2016)
Jan Lahney reviews: Michael Hyde, Hey Joe. The Vulgar Press, Canton North, 2003. Hyde, Michael, 1945- ISBN 0 9580794 4 7. I. Title. A823.3 Hey Joe - A novel for those too young to remember and those too old to forget